Analysis of Geographic and Historical Potential of Tumpak Rinjing Monument and Its Urgency as a Source of Historical Learning (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
This article describes the analysis of the geographical and historical potential of the Tumpak Rinjing Monument, located in the district of Pacitan as one of the memorials to historical events during the struggle for the physical revolution in Indonesia. Furthermore, this article also describes the urgency analysis of monuments as a source of local-based learning, especially for history learning. The method used is a historical and qualitative method with the type of research carried out is field research. The main finding in this study is that the geographical and historical potential of the existence of a hand-over batch monument is very supportive as a source of learning and learning